1979
DOI: 10.1038/bjc.1979.138
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution and tumour localization of 99m-technetium-labelled liposomes in cancer patients

Abstract: The possible use of liposomes (phospholipid vesicles) to direct cytotoxic drugs to tumours has led us to investigate the tissue localization of i.v. injected 99m-Tc-labelled liposomes in cancer patients. Twenty mg or 300 mg doses of liposomal lipid (7:2:1 molar ratio of phosphatidylcholine : cholesterol : phosphatidic acid) were used in a study of 13 patients with advanced cancer and one with polycythaemia rubra vera (PRV). In all cases except the patient with PRV the major site of uptake of the label was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 27 publications
(28 reference statements)
3
18
0
Order By: Relevance
“…In view of the changes in tissue distribution and bioavailability, it is uncertain whether the increased tolerated dosage of L-ADM will result in enhanced antitumour activity. In agreement with the human liposome imaging studies reported by Richardson et al (1979), the liposomes used here are cleared very quickly by the RES of liver and spleen and to a lesser extent by the bone marrow. Our studies suggest that the mechanism of antitumour activity of L-ADM is complex, and presumably results from exposure of tumour cells to drug leaking from circulating liposomes and drug released from the RES.…”
Section: Discussionsupporting
confidence: 89%
“…In view of the changes in tissue distribution and bioavailability, it is uncertain whether the increased tolerated dosage of L-ADM will result in enhanced antitumour activity. In agreement with the human liposome imaging studies reported by Richardson et al (1979), the liposomes used here are cleared very quickly by the RES of liver and spleen and to a lesser extent by the bone marrow. Our studies suggest that the mechanism of antitumour activity of L-ADM is complex, and presumably results from exposure of tumour cells to drug leaking from circulating liposomes and drug released from the RES.…”
Section: Discussionsupporting
confidence: 89%
“…Sometimes contradictory views related to the potential application of liposomes on a drug delivery system have been expressed [24]. The present study may contribute to the explanation of the varying re sults obtained according to the compound (its halflife, its stability in the presence of serum) and the schedule of the trials.…”
Section: Discussionmentioning
confidence: 69%
“…Although tumour localisation with 99mTc-technetium-labelled liposomes in the rat has been described (Richardson et al, 1977), various tumours in several patients were not visualised after injection with 99mTc-technetium-labelled liposomes (Richardson et al, 1979). This encourages us to think that 99mTc-technetium-labelled anionic liposomes may be specific for naturally occurring abscesses.…”
Section: Discussionmentioning
confidence: 98%